2016
DOI: 10.14740/jocmr2443w
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Anticoagulation and Dual Antiplatelet Therapy to the Outcomes of Patients With Atrial Fibrillation and Recent Percutaneous Coronary Intervention With Stent

Abstract: BackgroundChronic atrial fibrillation (AF), coexisting with a history of recent coronary angioplasty with stent (PCI-S), represents an encoded indication for oral anticoagulation (OAC) with warfarin plus dual antiplatelet therapy (DAPT).MethodsUsing a retrospective cohort study, we determined the respective impacts on cardiovascular outcomes of three different pharmacologic regimens, i.e., triple therapy (TT) with warfarin + clopidogrel and aspirin, dual therapy (DT) with warfarin + clopidogrel or aspirin, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…Fifteen studies ultimately met our inclusion criteria. Amongst 15 studies included, five were RCTs and 10 were observational . The study characteristics of individual studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifteen studies ultimately met our inclusion criteria. Amongst 15 studies included, five were RCTs and 10 were observational . The study characteristics of individual studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Amongst 15 studies included, five were RCTs 11,12,28-30 and 10 were observational. [22][23][24][25][26][27][28][29][30][31] The study characteristics of individual studies are presented in Table 2.…”
Section: Search Resultsmentioning
confidence: 99%
“…This is further supported by the recognition that bleeding events post‐PCI are associated with worse overall outcomes . Several studies have reported that the use of TAT results in similar rates of major adverse cardiovascular events (MACE) and major bleeding when compared to dual antithrombotic therapy (DAT) . However, many of these studies are observational and underpowered to detect such events.…”
Section: Changes Over the Past Decadementioning
confidence: 98%
“…2 Several studies have reported that the use of TAT results in similar rates of major adverse cardiovascular events (MACE) and major bleeding when compared to dual antithrombotic therapy (DAT). [3][4][5] However, many of these studies are observational and underpowered to detect such events. As a result, the optimal antithrombotic regimen post-PCI remains a subject of debate.…”
mentioning
confidence: 99%
“…Conversely, non-VKA oral anticoagulant (NOAC) without these deficiencies has dramatically optimized anticoagulation management. Although antithrombotic efficacy and bleeding risk of NOACs for AF patients undergoing PCI in the real world has not been well established yet, several clinical studies have yielded different results of several antiplatelet and anticoagulant regimens for these patients[620]. This systematic review and network meta-analysis (NMA) aimed to rank efficacy and safety of different antithrombotic therapies available for AF patients in post-PCI.…”
Section: Introductionmentioning
confidence: 99%